Give us the vote! : over 200 years of fighting for the ballot - Rubin, Susan Goldman (Holiday House, 2020)
Presents a historical account of the fight to gain the right to vote by women and minorities in the United States. Covers issues facing voters today, such as gerrymandering, and ways young activists have gotten involved. Includes photographs, political cartoons, a timeline, a list of Constitutional amendments, and resources for further reading.